Effect of underwater swimming on physiological and perceptual parameters in competitive swimmers: A comparison with surface swimming - Segovia-Sanbenito, C.; Guimard, A.; Fuente, B. D. L.; González-Frutos, P.; Veiga, S. (European Journal of Sport Science, 2026)
ABSTRACT In competition, swimmers alternate between swimming on the surface and underwater; they therefore train in apnea to improve their tolerance to lack of oxygen during exercise, even though research in this area remains limited. The aim of the study was to investigate the impact of underwater swimming on physiological and perceptual responses of competitive swimmers. Eighteen national level swimmers (700.25 ± 53.42 AQUA points) performed 6 × 25m maximal swimming efforts from a push start with 3 minutes rest in three different conditions: underwater (without breathing), surface (with normal breathing pattern) and competitive (composed of an underwater plus a surface swimming segment) swimming. Swimming performance (T25), gases exchange, heart rate (HR), arterial oxygen saturation (SpO 2 ), blood parameters, rating of perceived exertion (RPE) and subjective feeling (FS) were measured. The underwater condition produced a greater increase in blood lactate (Lac) ( p < 0.05; n2 = 0.67) and potassium ( p < 0.05; n2 = 0.35) than the surface and competitive conditions. No significant differences ( p > 0.05) were observed in HR, SpO 2 or RPE, whereas FS values were lower (more unpleasant) in the underwater swimming condition. However, oxygen uptake (VO2 ) was significantly lower ( p < 0.003; n2 = 0.09) ) in underwater than in competitive swimming. This study shows that a set of 25m underwater swimming efforts at maximum intensity generates an intense muscular, perceptive and metabolic demand in competitive swimmers, well tolerated by young trained competitive swimmers.